(untitled) (Journal of the College of Basic Education, 2026)
The aim of the research is to identify the effect of using the artificial intelligence (AI) application on complex thinking among fourth-grade science students in biology. To achieve the objective of this research, the following null hypothesis was formulated: There are no statistically significant differences at the (0.05) level between the mean scores of the experimental group students who will study using artificial intelligence (AI) and the mean scores of the control group students who will study using the traditional method in complex thinking for fourth-grade science students in biology. The researchers used an experimental design with partial control for two equivalent research groups. The research population consisted of fourth-year science students from all secondary schools for distinguished male and female students affiliated with the education directorates of Al-Rusafa II and I and Baghdad College. The researchers intentionally selected the sample for this research, which was Baghdad College secondary school, in order to conduct the research. The researchers chose Baghdad College High School intentionally. In order to conduct the research, the control research group and the experimental research group were randomly selected from among the six existing classes. Class (C) was the experimental class, which studied according to the application of artificial intelligence (AI), and Class (E) is a control group that studied according to the traditional teaching method.method and the sample number was (56) students. The research results showed that the experimental research group outperformed the control research group in complex thinking.